2020
DOI: 10.1186/s42077-020-00071-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bupivacaine versus bupivacaine-dexamethasone infiltration for postoperative analgesia in skin graft donor sites: a randomized trial

Abstract: Background Skin grafting, both partial and complete thickness, is frequently used in reconstruction of traumatic soft tissue defects. It is of great value not only for functional and anesthetic purposes in the field of plastic surgery, but also for other surgical specialties. Of all the problems in the early postoperative period, pain is considered the most important, ameliorating it can lead to significant reduction in postoperative morbidity and faster recovery of the skin donor site. Objective To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…43 Additionally, our study found that adding dexamethasone to ropivacaine in infiltration of the laminectomy surgical wound reduced the total dose of morphine consumed during the first post-operative 48 hours compared to the R-group, thereby reducing its side effects. Several studies in the literature have shown similar results, including one conducted in Ain Shams University Hospitals in Egypt from October 2018 to February 2019, 44 which evaluated the efficacy of dexamethasone as an adjuvant for bupivacaine in subcutaneous local anesthesia infiltration for skin graft donor sites. The study found that the total morphine consumption was significantly lower in the bupivacaine plus dexamethasone group than in the bupivacaine only group.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…43 Additionally, our study found that adding dexamethasone to ropivacaine in infiltration of the laminectomy surgical wound reduced the total dose of morphine consumed during the first post-operative 48 hours compared to the R-group, thereby reducing its side effects. Several studies in the literature have shown similar results, including one conducted in Ain Shams University Hospitals in Egypt from October 2018 to February 2019, 44 which evaluated the efficacy of dexamethasone as an adjuvant for bupivacaine in subcutaneous local anesthesia infiltration for skin graft donor sites. The study found that the total morphine consumption was significantly lower in the bupivacaine plus dexamethasone group than in the bupivacaine only group.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, there was a lower wound infection rate in the RD-group (0%) versus the R-group (0.7%, one patient). 31,42,44,47,[53][54][55][56][57][58] Therefore, dexamethasone as an adjuvant to incision-site infiltration is a safe method for the prevention of incision-site pain after spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis, based on the early diagnosis and treatment of CRPS, combined with the potential beneficial effect of sympathetic blocks for the treatment of CRPS and the analgesic effects of adding dexamethasone to bupivacaine for nerve blocks, showed that early diagnosis of CRPS of the foot and/or ankle and immediate adjunctive treatment with a ring-type anesthetic block of of the ankle consisting of bupivacaine mixed with dexamethasone may be beneficial (26)(27)(28)(29)(30). No case series or study considering this treatment regimen for CRPS of the foot or ankle was found in the literature.…”
Section: Introductionmentioning
confidence: 99%